Análise de impactos de um sistema fotovoltaico conectado à rede em Mossoró/RN - Balbino, Isaú Macêdo (Universidade Federal Rural do Semi-Árido, 2017)
Environmental problems, like global warming and pollution, together with the rising fossil fuels prices in recent years have increased search for alternative energy sources, that are clean and sustainable at the same time. Among the main sources, it is possible to highlight the photovoltaic solar energy. For being a source of clean renewable energy with a low maintenance rate, photovoltaic solar energy has been gaining attention worldwide, and with this the Grid-Connected Photovoltaic System (GCPV) has grown in the last decades. Despite the benefits from the GCPV, for being a relatively new technology when compared with other energy sources, the same is not yet fully consolidated, and its installation requires care in regard to quality of electrical power. Problems such as production of harmonics, overvoltage and low power factor are common to these types of systems. Several researches are conducted every year and regulations are created, in order to reconcile the photovoltaic generation with the power distribution network. Therefore, the present work aims to identify, measure and analyze the behavior of GCPV of 3 kWp of UFERSA, in the city of Mossoró-RN, in order to verify the possible impacts to the quality of the electric energy associated with GCPV. In this research it was noticed that all the parameters are within the current standard regulations, however the high indexes of harmonic distortion rate made necessary the elaboration of a low-pass filter to attenuate the unwanted frequencies. With the simulation of the filter in Simulink, an attenuation of up to more than 60% was verified, thus improving the quality of the energy generated by the system
Analysis of the Impacts of grid-connected photovoltaic system in Mossoró/RN
Keywords: Energia solar fotovoltaica; Sistemas fotovoltaicos conectados à rede; Problemas associados aos SFCR; Qualidade de energia elétrica; Filtro passa-baixa; Photovoltaic solar energy; Grid-connected photovoltaic system; Problems associated with GCPV; Quality of electrical energy; Low pass filter; ENGENHARIAS::ENGENHARIA ELETRICA